Embedding Scientific Explanations Into Storybooks Impacts Children’s Scientific Discourse and Learning - Leech, Kathryn A.; Haber, Amanda S.; Jalkh, Youmna; Corriveau, Kathleen H. (Frontiers in Psychology, 2020)
Children’s understanding of unobservable scientific entities largely depends on testimony from others, especially through parental explanations that highlight the mechanism underlying a scientific entity. Mechanistic explanations are particularly helpful in promoting children’s conceptual understanding, yet they are relatively rare in parent-child conversations. The current study aimed to increase parent-child use of mechanistic conversation by modeling this language in a storybook about the mechanism of electrical circuits. We also examined whether an increase in mechanistic conversation was associated with science learning outcomes, measured at both the dyadic- and child-level. In the current study, parents and their 4- to 5-year-old children (N = 60) were randomly assigned to read a book containing mechanistic explanations (n = 32) or one containing non-mechanistic explanations (n = 28). After reading the book together, parent-child joint understanding of electricity’s mechanism was tested by asking the dyad to assemble electrical components of a circuit toy so that a light would turn on. Finally, child science learning outcomes were examined by asking children to assemble a novel circuit toy and answer comprehension questions to gauge their understanding of electricity’s mechanism. Results indicate that dyads who read storybooks containing mechanistic explanations were 1) more successful at completing the circuit (putting the pieces together to make the light turn on) and 2) used more mechanistic language than dyads assigned to the non-mechanistic condition. Children in the mechanistic condition also had better learning outcomes, but only if they engaged in more mechanistic discourse with their parent. We discuss these results using a social interactionist framework to highlight the role of input and interaction for learning. We also highlight how these results implicate everyday routines such as book-reading in supporting children’s scientific discourse and understanding.